Presenilin Is Essential for ApoE Secretion, a Novel Role of Presenilin Involved in Alzheimer's Disease Pathogenesis - Islam, Sadequl; Sun, Yang; Gao, Yuan; Nakamura, Tomohisa; Noorani, Arshad Ali; Li, Tong; Wong, Philip C.; Kimura, Noriyuki; Matsubara, Etsuro; Kasuga, Kensaku; Ikeuchi, Takeshi; Tomita, Taisuke; et al. (The Journal of neuroscience, 2022)
Alzheimer's disease (AD) is a debilitating dementia characterized by progressive memory loss and aggregation of amyloid-β (Aβ) protein into amyloid plaques in patient brains. Mutations in presenilin (PS) lead to abnormal generation of Aβ, which is the major cause of familial AD (FAD), and apolipoprotein E4 (ApoE4) is the major genetic risk factor for sporadic AD (SAD) onset. However, whether dysfunction of PS is involved in the pathogenesis of SAD is largely unknown. We found that ApoE secretion was completely abolished in PS-deficient cells and markedly decreased by inhibition of γ-secretase activity. Blockade of γ-secretase activity by a γ-secretase inhibitor, DAPT, decreased ApoE secretion, suggesting an important role of γ-secretase activity in ApoE secretion. Reduced ApoE secretion is also observed in nicastrin-deficient cells with reduced γ-secretase activity. PS deficiency enhanced nuclear translocation of ApoE and binding of ApoE to importin α4, a nuclear transport receptor. Moreover, the expression of PS mutants in PS-deficient cells suppressed the restoration effects on ApoE secretion compared with the expression of wild-type PS. Plasma ApoE levels were lower in FAD patients carrying PS1 mutations compared with normal control subjects. Our findings suggest a novel role of PS contributing to the pathogenesis of SAD by regulating ApoE secretion. SIGNIFICANCE STATEMENT Familial AD (FAD) typically results from mutations in the genes encoding amyloid precursor protein, presenilin 1 (PS1), or PS2. Many PS mutants have been found to exert impaired γ-secretase activity and increased amyloid-β 42 (Aβ42)/Aβ40 ratio, which induce early amyloid deposition and FAD. On the other hand, apolipoprotein E4 (ApoE4) is the major genetic risk factor for sporadic AD (SAD) and contributes to AD pathogenesis because it has reduced Aβ clearance capability compared with ApoE3 and ApoE2. FAD and SAD have long been considered to be caused by these two independent mechanisms; however, for the first time, we demonstrated that PS is essential for ApoE secretion and PS mutants affected ApoE secretion in vitro and in human samples, suggesting a novel mechanism by which PS is also involved in SAD pathogenesis.